GRAMMATICAL COHESION OF PERSONAL PRONOUNS IN CHILDREN’S STORIES, ADOLESCENT STORIES, AND ADULT STORIES OF KOMPAS - Sukriyah, Siti; Sumarlam, Sumarlam; Djatmika, Djatmika (English Department FBS UNP, 2018)
This study aimed to describe the discourse coherence supported by aspects of gramatical cohesion is limited to the use of personal pronouns in the rubric of cernak, roman, and cerpen in Kompas Newspaper. this research belongs to descriptive qualitative. The data are obtained by review method with note technique as further technique. The data of this research are linguistic data taken from cernak, roman, and cerpen rubric of Kompas newspaper. The object of this research is personal pronouns grammatical cohesions in cernak, roman, and cerpen rubric of Kompas newspaper. Data analysis is done by identifying of the grammatical cohesion type of personal pronouns, then classify and describe the aspects of that grammatical cohesion. And then, the data is interpreted to get the conclusions. The results of this research that grammatical cohesion aspects of the personal pronouns in every rubric. the first, second, and third personal pronouns is found in every rubric. In the cernak is more likely has the form of the free third person as well as roman. Meanwhile, for the short story of adult has the plural third person because the plot of the short story of adult is more complex and have more figures than cernak or roman. The results of the data analysis showed that cernak, roman, and cerpen rubric of Kompas newspaper is a discourse coherent because it is supported by a slick lexical cohesion markers.Keywords: grammatical cohesion, Kompas, personal pronouns, rubric KOHESI GRAMATIKAL REFERENSI PRONOMINA PERSONA DALAM CERITA ANAK, CERITA REMAJA, DAN CERITA DEWASA PADA KOMPASAbstrakPenelitian ini bertujuan mendeskripsikan kepaduan wacana yang didukung oleh aspek kohesi gramatikal, dibatasi pada penggunaan referensi jenis pronomina persona dalam rubrik cernak, roman, dan cerpen pada Harian Kompas. Jenis penelitian ini bersifat deskriptif kualitatif. Penyediaan data menggunakan metode simak dengan teknik catat. Data dalam penelitian ini adalah data kebahasaan yang terdapat pada rubrik cernak, roman, dan cerpen pada Harian Kompas. Objek kajiannya adalah aspek kohesi gramatikal referensi pronomina persona yang terdapat dalam ketiga rubrik tersebut. Analisis data dilakukan dengan cara mengidentifikasi unsur kohesi gramatikal jenis referensi pronomina persona, selanjutnya mengklasifikasikan dan mendeskripsikan unsur kohesi gramatikal tersebut, kemudian data diinterpretasikan untuk mengambil kesimpulan. Pada hasil penelitian ditemukan aspek kohesi gramatikal referensi pronomina persona dalam setiap rubrik. Pada masing-masing rubrik ditemukan adanya referensi jenis pronomina persona I, II, dan III. Pada teks cerita anak (cernak) lebih cenderung menggunakan pronomina persona ketiga tunggal bentuk bebas; demikian pula untuk cerita remaja (roman). Sementara itu, untuk cerita dewasa (cerpen) cenderung lebih sering menggunakan pronomina persona ketiga jamak karena cerita dewasa atau cerpen jalinan ceritanya lebih kompleks dan melibatkan banyak tokoh (pelaku) dibandingkan dengan cernak maupun roman. Berdasarkan hasil analisis data, dapat disimpulkan bahwa rubrik cernak, roman, dan cerpen dalam surat kabar Harian Kompas merupakan sebuah wacana yang padu karena di dukung oleh penanda kohesi gramatikal yang apik.Kata kunci: kohesi gramatikal, Kompas, referensi persona, rubrik